PELEMBAGAAN MULTIKULTURALISME MELALUI METODE LIVING VALUES DI MADRASAH: SEBUAH EKSPLORASI AWAL - Syamsul Arifin (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2008)
The aim of this article is to anake the institutionalization of multiculturalism by means of the method of living values in madrasah. As apart of education institution, madrasah has a moral obligation to evolve the students insights concerned with the problem of plurality in society particularly in religious aspect. Dealing with the multicultural values development, this article tries to offer the way of how to institutionalize any multicultural values as a theoretical base to develop the multicultural education in madrasah.